Dr. Hüray Karaca — Deep Plane Facelift — İzmir - Karaca, Hüray (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Hüray Karaca, practicing in İzmir, Turkey. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003324; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; turkey; i̇zmir